PEMBELAJARAN DARING BERBASIS E-LEARNING (DEMIA) PADA SISWA SMKS AHLU SUFFAH MUHAMMADIYAH BANTAENG - Andi Asvin Mahersatillah Suradi; Mushaf; Muhammad Syukri Mustafa; Salmiati; Marsa (LPPM Universitas Al Muslim, 2023)
E-learning based learning is a method using information and communication technology (ICT) as a learning tool. This method allows students to study independently, without being bound by limited time and space. E-learning-based learning requires students to access learning materials via the internet, do assignments, and interact directly with teachers or fellow students through discussion forums or video conferencing. E-learning increases learning effectiveness and provides easier and more flexible access to education for students and teaching staff. In addition, teachers can provide feedback and assess student learning outcomes in real time through the available system. This PKM activity was carried out at SMKS Ahlu Suffah Muhammadiyah Kab. Bantaeng on November 30 2022 at 08.00-16.00 WITA with 32 participants. The target audience were the students and teachers of SMKS Ahlu Suffah Muhammadiyah Kab. Bantaeng. The resource persons for this activity were UNDIPA Makassar lecturers. The assistance run smoothly since it applied alternative problem-solving methods, especially assistance through a classic individual approach, which is applied when delivering material related to LMS